Arbitral Institutions Under Scrutiny - Philipp Habegger (JurisNet, 2013)
The internal organisation and practices of operation of arbitral institutions are often not transparent and are rarely addressed in public discussions among arbitration practitioners. To shed some light on aspects of the internal organisation and operation of these institutions, ASA asked the MIDS (Geneva LLM in International Dispute Settlement) to conduct a broad survey of arbitral institutions based on a detailed questionnaire. The results are summarized in Chapter 1 of this volume